Population structure in Al-Rifai district for the period (2009-2019 - Gallab, Ass.Lecture Abdulnabi Hussein (Thi Qar Arts Journal, 2021)
The study of the characteristics of the population, especially the composition, is one of the vital studies because of its great importance in influencing the overall activity of the population on the one hand, and the volume of services it needs on the other hand, in the present and the future. The research aims to know the extent to which the population is environmentally and qualitatively stable and classified demographically. The research followed the descriptive analytical approach and relied on population estimates issued by the Directorate of Statistics of Thi-Qar, which were represented by tables, charts and maps by adopting GIS technology. She suggested the proportion of the urban population with a decrease in the proportion for the year 2019 than in 2009 for both environments, and indicated that the children’s category is the largest group, which represents a broad base in the population pyramid